PERAN METODE PEMBELAJARAN TERHADAP KUALITAS BELAJAR MATERI SEJARAH HINDU-BUDDHA DAN ISLAM DI INDONESIA - Salsabila, Suzahra; Sari, Lala Karmila; Arifin, Muh. Husen; Wahyuningsih, Yona (Universitas Pakuan, 2021)
THE ROLE OF LEARNING METHODS ON THE QUALITY OF LEARNING HINDU-BUDDHIST AND ISLAMIC HISTORY MATERIALS IN INDONESIAThe achievement of learning objectives is one of the objectives of the learning method. In this case the learning method is used to realize the design that has been prepared. The purpose of this paper is that educators can implement several different methods in social studies learning in material about the heritage of Hinduism, Buddhism, and Islam in Indonesia. The method in this writing uses a literature study method, where researchers use existing books, magazines, articles, and journals that are related and relevant to the research topic taken. The results of this study are methods that can be used and improve the quality of learning in social studies learning material heritage of Hinduism, Buddhism, and Islam in Indonesia, namely the discussion method, simulation method, assignment method, Mind Mapping, field trip method.